PENGEMBANGAN BAHAN AJAR E-MODUL BERBASIS INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF MATERI SISTEM PENCERNAAN MANUSIA : e-modul, inkuiri terbimbing, sistem pencernaan manusia - zulfitri, eka; Widowati, Hening; Muhfahroyin (BIOLOVA, 2025)
This research aims to develop intuition-based E-modules that can be used to improve cognitive learning outcomes on human learning materials for science subjects in class VIII in junior high school. This study also aims to assess the effectiveness of the developed E-module and measure its learning outcomes. This development research involves the process described by Thiagarajan and consists of four stages, namely defining (Define), designing (Design), developing (Develop), and disseminating (Disseminate). The subjects of the small group trial consisted of 10 samples of students in class VIII of SMP Ma'arif 9 Seputih Banyak and the field trial subjects were 25 samples of students in class VIII of SMP Ma'arif 9 Seputih Banyak. Data collection instruments used assessment sheets in the form of response questionnaires and cognitive learning outcomes tests. The data analysis technique used paired sample t-test. The results of the research show that the guided inquiry-based E-Module can improve cognitive learning outcomes on human digestive system material for class VIII SMP according to design experts, linguists and material experts in Very Good criteria with a percentage of design expert validation of 90%, linguist validation of 90%. 89%, material expert validation, namely 90%, and received a positive response from students, namely with a percentage of 90% with Very Good criteria. There is a difference in the pretest learning results before using the E-Module, namely with an average of 76 and posttest after using the E-Module, namely with an average of 95, the N-gain score is 0.8 with a high interpretation.